The high house : a novel - Greengrass, Jessie, 1982- (Scribner, 2022)
Francesca is Caro's stepmother, and Pauly's mother. A scientist, she can see what is going to happen. The high house was once her holiday home; now looked after by locals Grandy and Sally, she has turned it into an ark, for when the time comes. The mill powers the generator; the orchard is carefully pruned; the greenhouse has all its glass intact. Almost a family, but not quite, they plant, store seed, and watch the weather carefully.